Output Quotas in Imperfect Cartels - Bain, Joe S. (Quarterly Journal of Economics, 1948)
Journal Article Output Quotas in Imperfect Cartels Get access Joe S. Bain Joe S. Bain University of California, Berkeley, California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 62, Issue 4, August 1948, Pages 617–622, https://doi.org/10.2307/1881769 Published: 01 August 1948